2017
DOI: 10.1371/journal.ppat.1006577
|View full text |Cite
|
Sign up to set email alerts
|

Innate activation of human primary epithelial cells broadens the host response to Mycobacterium tuberculosis in the airways

Abstract: Early events in the human airways determining whether exposure to Mycobacterium tuberculosis (Mtb) results in acquisition of infection are poorly understood. Epithelial cells are the dominant cell type in the lungs, but little is known about their role in tuberculosis. We hypothesised that human primary airway epithelial cells are part of the first line of defense against Mtb-infection and contribute to the protective host response in the human respiratory tract. We modelled these early airway-interactions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 60 publications
2
51
0
Order By: Relevance
“…Mycobacterial cell walls contain multiple peptidoglycans including D-glucosamine and a mycolic acid layer (5) that initiate the interaction between bacteria and host upon inhalation (6). Macrophages are a critical immune cell in combatting mycobacterial infections with a significant proportion of their response dependent on type I IFN signaling (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Mycobacterial cell walls contain multiple peptidoglycans including D-glucosamine and a mycolic acid layer (5) that initiate the interaction between bacteria and host upon inhalation (6). Macrophages are a critical immune cell in combatting mycobacterial infections with a significant proportion of their response dependent on type I IFN signaling (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In zebrafish these responses result in bacterial clearance (Cambier et al, 2014b), highlighting this pathway as a conserved response to infection. In contrast, human epithelial cells infected by mycobacteria have no significant change in global transcription, suggesting minimal immune detection (Reuschl et al, 2017). Our data now demonstrate that PDIM plays a role in silencing epithelial cell responses, promoting uptake by non-activated macrophages.…”
Section: Discussionmentioning
confidence: 65%
“…Of note, the epithelial cell-mediated attenuation of Mtb -induced TLR-mediated inflammatory responses in U937 macrophage-like cells was cell contact independent, suggesting that the contact-independent communication between alveolar epithelial cells reduced immune responses of macrophages to Mtb in an early stage of infections. Indeed, such an early immune interaction of epithelial cells and macrophages was recently confirmed in another study by using a coculture model of human primary bronchial epithelial cells (PBECs) and THP-1 monocytes, in which the epithelial cells were found to express the same transcriptomic pattern in response to Mtb infection to that of alveolar macrophages or THP-1 cells [ 28 ]. By using this novel model, the authors demonstrated that PBECs were inert to direct Mtb -infection and not potent responders in an IL-1 β - and type I interferon- (IFN-) mediated Mtb -activated immune network.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, there is a substantial evidence for interactions between alveolar epithelial cells and macrophages in alveolar sacs [ 2 ]. In this respect, alveolar epithelial cells are an important source of cytokines and mediators modulating the phenotype or activation of alveolar macrophages in response to an external stimulus, including the Mtb [ 2 , 5 , 10 , 28 ]. A previous coculture study using Mono-Mac-6 Mphis (MM6-Mphis) macrophages and epithelial A549 cells demonstrated that a direct cell contact between epithelial cells and macrophages led a decreased intracellular growth of Mtb in infected macrophages, despite that the bacterial growth in A549 cells was not affected [ 29 ].…”
Section: Discussionmentioning
confidence: 99%